Praxis of the offence of fleeing the scene of an accident in art. 382 bis criminal code (Organic Law 2/2019 of 1 march 2019 and Organic Law 11/2022 of 13 september). - Magro Servet, Vicente (Logos Guardia Civil, Scientific Magazine of the University Center of the Guardia Civil, 2024)
Analysis about the characteristics and circumstances of the crime of escape from the place of the accident that was incorporated into the criminal text in LO 2/2019 of March 1, modified by LO 11/2022, of September 13, with the purpose of avoid situations of impunity when a driver hit another with his vehicle and died on the spot and fled, not being able, in addition to reckless homicide, or eventual intentional homicide if the circumstances arose, to qualify it before this reform as an omission of the duty to help if the victim had died. Supreme Court Judgment 1/2023 of January 18, analyzing whether the attempt is possible in these cases
Keywords: Crime of escape from the place of the accident; act of God; recklessness